Behavior of non-autonomous oscillating system under the influence of small random perturbations in the resonance case - Borisenko , О. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The limiting behavior of a solution of a nonlinear stochastic differential equation describing a nonautonomous oscillatory system with small random perturbations is investigated. The resonance case is considered.